The relationship between customer experience with customer satisfaction and online customer review in buying the product in tokopedia - Gara, Gd Pandya Wicaksana; Nasution, Reza Ashari (Journal of Business and Management, 2020)
Abstract. Tokopedia is one of the most widely used online platforms by the public. This research aimed at determining 1) the relationship between online customer review and customer experience in buying the product in Tokopedia 2) the relationship between online customer review and customer satisfaction in buying the product in Tokopedia, 3) the relationship between customer experience and customer satisfaction in buying the product in Tokopedia. The population of this study was Tokopedia users since January 2020 until June 2020 in Bandung Raya. The sample were 100 respondents who were selected using Purposive Sampling Technique. Due to the Pandemic Covid-19, the data were gained only from the distribution of the questionnaire through Line, Instagram and WhatsApp. Classical Assumption Test and Multiple Linear Regression methods were used to analyze the data assisted by SPSS. Based on the research that had been conducted, the results showed that 1) There was a positive relationship between online customer review and customer experience in buying the product in Tokopedia, 2) There was a positive relationship between online customer review and customersatisfaction in buying the product in Tokopedia, 3) There was a positive relationship between customer experience and customer satisfaction in buying the product in Tokopedia.Keywords: Online Customer Review, Customer Experience, Customer Satisfaction, Tokopedia.